System Dynamics and Simulation/Gaming: Overview. (June 2015) - Alessi, Stephen; Kopainsky, Birgit
Purpose . This article summarizes the nine contributions to thesymposium on system dynamics . The goal of the symposium is to investigate how research in system dynamics iscontributing to simulation-gaming, and how the more general field of simulation-gaming isinfluencing work in system dynamics. Summary of articles . We summarize the nine contributions. They include five articles on basic research inlearning and teachingprinciples for system dynamics, three articles oninteractive learning environments, and a finalcritical reflection article which summarizes the other eight and suggests future research needs. Conclusion . The main problem still to be addressed isimprovement in andmeasurement oflearning andperformance .